The Pontential of Using Citrullus Lanatus, Moringa Oleifera And Hibiscus as Natural Coagulant for Wastewater Treatment - Nur Aisyaa Ayop,; Nurul Aina Najwa Ruslan,; Mohd Aripen, Nur shahirah (Multidisciplinary Applied Research and Innovation, 2024)
Natural coagulant wastewater treatment methods are gaining popularity  due to their environmentally friendly method which can reduce  the effluent treatment footprint and lack of toxicity compared to chemical coagulant. Hence, this research evaluated the potential of the moringa oleifera, hibiscus seeds and citrullus lanatus as a natural coagulant. All of these plant was used for the treatment of leachate industrial wastewater samples. Experimental tests were performed to evaluate the efficiency of natural coagulant based on pH reduction and turbidity removal. The studies was run by jar test experiment with two methods which are run based on different ratio of coagulant with alum and speed of rotation of jar test in range between 10-40 rpm. Results demonstrated that the hibiscus shows the highest turbidity removal and pH reduction percentage at 10 rpm speed of rotation which are 24.2% and 99.6% respectively. Following that, at 0.1g of moringa oleifera coagulant dosage, there was a significant decrease in both parameters, with an average turbidity and pH reduction percentage of 13.6% and 3.5% respectively. Hence the lowest the speed of rotation, the effective of coagulant decreases and the lower amount of natural coagulant dosage used the higher the percentage turbidity and pH reduction.